Hubungan Pemberian Asi Eksklusif Dengan Pertumbuhan Dan Perkembangan Pada Bayi Usia 6-12 Bulan Di PMB Evi Liana Kecamatan Pegajahan Kabupaten Serdang Bedagai Tahun 2023 - Evi Liana; Nopalina Suyanti Damanik; Eka Falentina Tarigan; Eka Purnamasari (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
To support exclusive breastfeeding in Indonesia, the government launched the National Movement to Increase Breastfeeding (PP-ASI), one of the aims of which is to cultivate exclusive breastfeeding behavior for babies up to 4 months old. In 2004, in accordance with recommendations from the World Health Organization (WHO), exclusive breastfeeding was increased to 6 months as stated in the Decree of the Minister of Health of the Republic of Indonesia number 450/MENKES/SK/VI/2004 (Ministry of Health of the Republic of Indonesia, 2021). This study aims to analyze the relationship between exclusive breastfeeding and growth and development in babies aged 6-12 months in PMB Evi Liana, Pegajahan District, Serdang Bedagai Regency in 2023. This research is correlational with a cross sectional approach and bivariate data analysis is the data analysis used in research to determine the relationship or influence of the independent variable with the dependent variable using Chi Square analysis with a significant p-value (0.05) (Hardani, 2020)Based on the results of research on exclusive breastfeeding for growth in babies aged 6-12 months in PMB Evi Liana, Pegajahan District, Serdang Bedagai Regency in 2023 with a p-value of 0.000. Based on exclusive breastfeeding with development in babies aged 6-12 months in PMB Evi Liana, Pegajahan District, Serdang Bedagai Regency in 2023 with a p-value of 0.000.This means that there is a relationship between exclusive breastfeeding and growth and development in babies aged 6-12 months at PMB Evi Liana, Pegajahan District, Serdang Bedagai Regency in 2023.